RANCANG BANGUN DAN UJI COBA ENGINE CLEANER SEBAGAI PENUNJANG PRAKTEK TEKNOLOGI MOTOR BENSIN - Sumardi Sumardi; Soleh Soleh; Okky Ardiansyah Prabowo (Otopro, 2022)
Overhaul is one of the activities carried out to restore engine performance so that it appears close to its previous condition both in terms of power and fuel consumption. In carrying out an overhaul, ideally, the engine components must first be cleaned of scale and dirt. Referring to these problems, the purpose of this research is to design an engine cleaner technology which is used as an alternative solution. Through the engine cleaner, the gasoline waste from the rinse will be processed so that it does not pollute the environment. This research is a design type which is carried out by considering several factors such as design, strength, ergonomics, material requirements and cost. The research data analysis technique refers to quantitative descriptive. The research data is then presented in the form of a bar chart according to predetermined indicators to measure the efficiency and quality of the engine cleaner. Based on the results of the research, the engine clear technology functions according to the design results. In addition, in terms of convenience and usefulness, both lecturers and students are greatly helped by this technology so that in the process of cleaning machine components. Thus, the process of cleaning the components of the practicum machine is cleaner than cleaning manually.